Water/Ethanol Soluble p-Type Conjugated Polymers for the Use in Organic Photovoltaics - Pan, Xun; Sharma, Anirudh; Kroon, Renee; Gedefaw, Desta; Elmas, Sait; Yin, Yanting; Andersson, Gunther G.; Lewis, David A.; Andersson, Mats R. (Frontiers in Materials, 2020)
We have developed two series of p-type conjugated polymers based on poly[2,3-bis-(3-octyloxyphenyl)quinoxaline-5,8-diyl-alt-thiophene-2,5-diyl] (TQ1) polymeric backbone utilizing polar pendant groups, i.e. tertiary amine and pyridine, to achieve switchable solubility in water and ethanol. By balancing the ratio between polar and non-polar side-groups, we could combine green-solvent processability with the manufacturing of functional photovoltaic devices. Due to the unavailability of water/alcohol soluble acceptors, the photovoltaic performance of these new polymers was evaluated using organic solvent by incorporating PC61BM. For partial amine-based polymers, we achieve a maximum power conversion efficiency (PCE) of 0.8% whereas partial pyridine-based polymers show enhanced PCE of 1.3% with inverted device structure. We propose that the enhancement in PCE is a result of the reduction in amino-group content and the lower basicity of pyridine, both of which decrease the interaction between functionalized polymers with the anode interface material and reduce the miscibility of the donor and acceptor. Further improvement of the photovoltaic performance, in particular the open-circuit voltage (Voc), was achieved by using an anode buffer layer to mitigate the unfavorable interaction of the amino/pyridine groups with the MoO3 electrode. Our work demonstrated the possibility of substituent modification for conjugated polymers using tertiary amine and pyridine groups to achieve water/alcohol soluble and functional donor materials.